2015
DOI: 10.1074/jbc.m115.668913
|View full text |Cite
|
Sign up to set email alerts
|

Role of a Hydrophobic Pocket in Polyamine Interactions with the Polyspecific Organic Cation Transporter OCT3

Abstract: Background: OCT3 pharmacology is distinct from that of other OCTs, which may relate to non-conserved residues in a putative binding pocket. Results: Mutating pocket residues to their OCT1 counterparts shifts OCT3 polyamine-like blocker sensitivity toward that of OCT1, and vice versa. Conclusion: OCT substrate-recognition mechanisms are fine-tuned by the makeup of the binding cleft. Significance: A mechanism has not yet been proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Sala-Rabanal et al have been reported that MPP + transport via mouse OCT1-2 and rat OCT3 was not significantly inhibited by 1 mM spermine, 26) although rat OCT1, 17) human OCT2, 18) and human/rat OCT3 19) accept spermine as a substrate or inhibitor. Among these OCTs, it has been reported that OCT3 is localized on the CSF side of choroid plexus epithelial cells in rats, and is involved in creatinine transport from the CSF to the cells.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Sala-Rabanal et al have been reported that MPP + transport via mouse OCT1-2 and rat OCT3 was not significantly inhibited by 1 mM spermine, 26) although rat OCT1, 17) human OCT2, 18) and human/rat OCT3 19) accept spermine as a substrate or inhibitor. Among these OCTs, it has been reported that OCT3 is localized on the CSF side of choroid plexus epithelial cells in rats, and is involved in creatinine transport from the CSF to the cells.…”
Section: Resultsmentioning
confidence: 98%
“…Among the transporters which are expressed at the BBB and BCSFB, OCT1-3 accepts spermine as a substrate/inhibitor with an affinity of more than 1 mM. [17][18][19] However, spermine transport at the BBB/BCSFB and the responsible molecule(s) for this process are unknown.…”
mentioning
confidence: 99%
“…Since PA uptake, N-acetylation, and release are key aspects of HAND, it is important to understand how PAs enter cells. On the basis of previous publications on PA permeability via large pores such as connexin-43 (Cx43) [37][38][39] and published data on PA transport [40], we identified two strong candidate proteins for PA transport in astrocytes: organic cation transporters (OCTs) and Cx43 hemichannels (HCs). OCTs are transmembrane proteins that belong to the solute carrier family 22 (SLC22A1-3) of polyspecific facilitative transporters.…”
Section: Introductionmentioning
confidence: 99%
“…OCTs are transmembrane proteins that belong to the solute carrier family 22 (SLC22A1-3) of polyspecific facilitative transporters. They mediate the uptake, distribution, and efflux of organic cations including PAs across the cell membrane [40][41][42]. Of this family of proteins, OCT3 is expressed in astrocytes [43] and has been shown to transport PAs [40,42].…”
Section: Introductionmentioning
confidence: 99%
“… 13 15 These models suggest that transporters undergo a series of conformational changes like an outward-open conformation, occluded state, and inward-open conformation to perform substrate translocation. 16 However, how the conformational changes get activated and achieved is still not clear. Although the intracellular loop between 6 and 7 of the SLC22 family was proved to be critical for the conformational change, 17 this rigid movement is considered to be insufficient to clarify the translocation processes.…”
Section: Introductionmentioning
confidence: 99%